Screening of Gestational diabetes mellitus - Farid, Gehan; Ali, Sarah Rabie; Kamal, Reem Mohammed (Clinical Journal of Obstetrics and Gynecology, 2018)
Gestational diabetes mellitus is becoming a very common medical disorder associated with pregnancy especially so in the Middle East and more so in Saudi Arabia, thus putting the women and fetuses at an increased risk of maternal and neonatal morbidity and mortality. Screening for Gestational diabetes mellitus was recommended because of its asymptomatic nature and good proportion of patients with no classic risk factors. We recommended universal screening because of the beneficial effect of screening, diagnosis and subsequent treatment. The most recent study done in Security Forces Hospital showed a significant decrease in morbidity and mortality with application of the new values of screening, in spite of the increase of incidence of Gestational diabetes mellitus from 14.5 % in 2005 study, to 23.9 % in the recent study in 2015. Objectives: To highlight and determine the best screening method values of FBS and 2hrspp used to diagnose gestational diabetes mellitus. Maternal & neonatal out come and associated risks for patients who had Gestational diabetes mellitus, where scrutinized. The study was done in the period from June 1st 2013-31 of May 2014. Design: Retrospective cohort study. Setting: Tertiary centre (Security Forces hospital _Riyadh_Saudi Arabia). Patients: Out of 6849 patients who had their delivery in Security Forces Hospital between June 2013 and May 2014 (one year), 6340 patients (92.5 %) were screened for gestational diabetes mellitus, and out of these 1516 patients (23.9 %) were labeled as Gestational diabetes mellitus after exclusion of cases of IDDM and NIDDM. Main outcome measured: The purpose of this study is to advise on using new values for diagnosis of gestational diabetes and to assess the outcome of pregnancy after new values are implemented in security forces hospital for diagnosis. The outcome included ages of mothers, parities, number of abortions, associated medical disorders, and estimated blood loss. Control methods were also reviewed, gestational age of induction of labor. Associated intrapartum complications as well as fetal outcome were also reviewed. The weight of babies, congenital abnormalities, admission to neonatal intensive care unit were also studied. The different values used , and percentages of diagnosed values of last 3 studies done in Security Forces Hospital in comparison to the most recent study with new values(2014-2015) as shown in table 11. Results: The incidence of gestational diabetes mellitus increased from 14.5 % in the year 2003 - 2004 to reach 23.9 % in 2014, in the same institute (Security Forces Hospital), where the study was done using different values. In our study in Security Forces Hospital we recorded a significant decrease in morbidity and mortality on applying the new values. A significant reduction in the number of expired babies of mothers who were diagnosed as gestational diabetes with new values with a decrease from 5.6 % in previous years studied to reach 1.5 % in 2014, reflecting the effective control and the good catch for the new values. Conclusion: Universal screening, with whatever values to blood sugar used, is a better method screening than the selective one: Using 75 gram of Oral Glucose Tolerance Test proved to be cost effective, easily accessible, and with good pickup rate of up to 93 % of patients in Security Forces Hospital. Recommendations: To continue using the new values that will be universally implemented, with long term follow-up of mothers and newborn